2020
DOI: 10.2196/16699
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Cardiovascular Disease Among Urban African Americans With a Mobile Health App (the MOYO App): Protocol for a Usability Study

Abstract: Background Cardiovascular disease (CVD) disparities are a particularly devastating manifestation of health inequity. Despite advancements in prevention and treatment, CVD is still the leading cause of death in the United States. Additionally, research indicates that African American (AA) and other ethnic-minority populations are affected by CVD at earlier ages than white Americans. Given that AAs are the fastest-growing population of smartphon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…O trabalho "Preventing cardiovascular disease among urban african americans with a mobile health app (the MOYO app): Protocol for a usability study" (12) (PubMed) teve como objetivo desenvolver e avaliar a eficácia de um novo aplicativo de smartphone projetado para reduzir os fatores de risco de doenças cardiovasculares entre americanos de origem africana de 18 a 29 anos de idade que moram em cidades. O aplicativo foi desenvolvido utilizando métodos de design participativos baseados na comunidade.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…O trabalho "Preventing cardiovascular disease among urban african americans with a mobile health app (the MOYO app): Protocol for a usability study" (12) (PubMed) teve como objetivo desenvolver e avaliar a eficácia de um novo aplicativo de smartphone projetado para reduzir os fatores de risco de doenças cardiovasculares entre americanos de origem africana de 18 a 29 anos de idade que moram em cidades. O aplicativo foi desenvolvido utilizando métodos de design participativos baseados na comunidade.…”
Section: Resultsunclassified
“…Em relação aos métodos utilizados para desenvolvimento de aplicativos móveis na área da saúde destaca-se que nos trabalhos (11,12,15,21) utilizaram a metodologia denominada design centrado no usuário dando destaque para participação da comunidade no desenvolvimento dos aplicativos.…”
Section: No Trabalho "Interactive Voice Response Service To Improve H...unclassified
See 1 more Smart Citation
“…In the MOYO study, researchers combined the health belief model and social cognitive theory with a CBPR approach to successfully design a CVH intervention for AA youth. 44 In their mHealth intervention to increase PA among AA women, Rodney and colleagues utilized social cognitive theory mediators to guide the data collection on the feasibility and acceptability of the intervention. Thus, our approach is in line with methods used in other mHealth usability studies for interventions among AAs 12 , 44 , 45 and represents a model of a successful community–academic partnership.…”
Section: Discussionmentioning
confidence: 99%
“…As SCT-MC has been used in numerous studies to explore the behavioral acceptance of communications interventions among minority communities, the case can be made for using SCT-MC to evaluate feasibility within a group that has been relatively understudied. Research guided by this framework has identified the benefits of using mobile apps to deliver evidence-based health messaging and training [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%